The role of the binary lesson in the teaching of professional kazakh language (Eurasian Journal of Philology Science and Education, 2016)
The article deals with the type of non-traditional lesson as a binary, its characteristics, objectives and main goals on the theoretical bases. Binary lesson is the optimal form of teaching professional Kazakh language to students, studying the Kazakh language as a foreign language. During binary lesson, students act as future professionals and receive information in the Kazakh language from a specialist. It helps the student to study, to explore and encourages him to learn. Also in the article, the authors give types of binary classes. Along with the theory and types of binary lesson reveals the features of its main object.
Keywords: binary lesson; integration; education; types of lessons; communicative competence